2017
DOI: 10.1063/1.4978054
|View full text |Cite|
|
Sign up to set email alerts
|

Network confinement and heterogeneity slows nanoparticle diffusion in polymer gels

Abstract: Nanoparticle (NP) diffusion was measured in polyacrylamide gels (PAGs) with a mesh size comparable to the NP size, 21 nm. The confinement ratio (CR), NP diameter/mesh size, increased from 0.4 to 3.8 by increasing crosslinker density and from 0.4 to 2.1 by adding acetone, which collapsed the PAGs. In all gels, NPs either became localized, moving less than 200 nm, diffused microns, or exhibited a combination of these behaviors, as measured by single particle tracking. Mean squared displacements (MSDs) of mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 55 publications
5
67
0
1
Order By: Relevance
“…At the initial ballistic regime (τ < 0.1 µs), the MSD is independent of the polymer concentration, because the polymers do not interact with the NPs at short times, thus having little impact on the motion of NPs. The results are in close qualitative agreement with available experimental results [37,38]. Correspondingly, we present the VACF and diffusion coefficient of NPs in Figure 3(a).…”
Section: Effect Of Polymer Concentration On Np Diffusionsupporting
confidence: 90%
See 1 more Smart Citation
“…At the initial ballistic regime (τ < 0.1 µs), the MSD is independent of the polymer concentration, because the polymers do not interact with the NPs at short times, thus having little impact on the motion of NPs. The results are in close qualitative agreement with available experimental results [37,38]. Correspondingly, we present the VACF and diffusion coefficient of NPs in Figure 3(a).…”
Section: Effect Of Polymer Concentration On Np Diffusionsupporting
confidence: 90%
“…To quantify the confinement of polymer network on NPs, we introduce the van Hove displacement distributions [37,38,58,59], which characterize the probability distribution of the distance a particle moving along x, y or z direction and can be calculated based on [59]:…”
Section: Effect Of Polymer Concentration On Np Diffusionmentioning
confidence: 99%
“…Accordingly, previous studies on tracer diffusion in polymer networks have focused on understanding the effect of different network mesh sizes [7][8][9]19,[24][25][26][27][28][29][30][31]. For instance, recent experiments on tracer diffusion in hydrogels investigated the effect of changes in ξ by varying the degree of crosslinking and by volume phase transition [7][8][9]19,26,31]. ξ decreases with an increasing degree of crosslinking and with a decrease in swelling ratio, and it was shown that the diffusion of a tracer particle in hydrogels, with variable crosslinking or swelling, is largely determined by ξ relative to the size of a tracer particle σ tr , i.e., ξ/σ tr .…”
Section: Introductionmentioning
confidence: 99%
“…ξ decreases with an increasing degree of crosslinking and with a decrease in swelling ratio, and it was shown that the diffusion of a tracer particle in hydrogels, with variable crosslinking or swelling, is largely determined by ξ relative to the size of a tracer particle σ tr , i.e., ξ/σ tr . However, the systematic and quantitative investigation on the relation between tracer diffusion and the ratio of ξ/σ tr has been complicated due to the heterogeneity inherent in the polymer networks during the course of crosslinking or volume phase transition [19,31,32]. Computer simulations of polymer models, on the other hand, allow for the preparation of regularly crosslinked, homogeneous polymer networks and the investigation of tracer diffusion in the absence of network heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation